Challenges and Prospects of Applying Scientific Methods in Sociological and Policy Investigation - Okon, Bassey, Antigha; Aya, Abang, Thelma; Eru, IJI, Mary (International Journal of Emerging Trends in Social Sciences, 2017)
The paper examines sociological and policy investigations, in terms of its method of inquiry and the possibility of applying scientific methods. Major tools, techniques and methods of science were highlighted and discussed showing their extent of application in Sociology and Policy Studies. The paper maintains the stand that both disciplines as Social Sciences utilized scientific methods and identified measurement difficulties, subjectivity and methodological crises as their major limitations as sciences. It concluded that though theory building and experimentation are not possible in social sciences, the adaptation of observation, quantification, identification of problem, hypothesis formulation and testing, position both Sociology and Policy Study as sciences. It is expected that with the passage of time, Sociology and Policy Studies will reveal their full scientific attributes. It was recommended that scientific methods should be explored and utilized in all social sciences extensively.